Homology of amino acid sequences of rat liver cathepsins B and H with that of papain. - Takio, K (1983)
The amino acid sequences of rat liver lysosomal thiol endopeptidases, cathepsins B and H, are presented and compared with that of the plant thiol protease papain. The 252-residue sequence of cathepsin B and the 220-residue sequence of cathepsin H were determined largely by automated Edman degradation of their intact polypeptide chains and of the two chains of each enzyme generated by limited proteolysis. Subfragments of the chains were produced by enzymatic digestion and by chemical cleavage of methionyl and tryptophanyl bonds. Comparison of the amino acid sequences of cathepsins B and H with each other and with that of papain demonstrates a striking homology among their primary structures. Sequence identity is extremely high in regions which, according to the three-dimensional structure of papain, constitute the catalytic site. The results not only reveal the first structural features of mammalian thiol endopeptidases but also provide insight into the evolutionary relationships among plant and mammalian thiol proteases.